Implementation of Indirect Evidence on Tender Conspiracy in The Construction Services: How to Prove it? - Yusro, Mochammad Abizar; Hakimah , Arista Salsabila; Edeline, Aurora (Indonesia Law Reform Journal, 2024)
In the current government era, the focus on infrastructure development is carried out to increase competitiveness on a national and international scale. Tthe realisation of the infrastructure budget in 2021 reached IDR 402.8 trillion, growing 31.1% compared to 2020. However, it is not uncommon for irregularities to occur in preparing and implementing infrastructure development, one of which is a tender conspiracy in the construction services sector. Difficult proof becomes an obstacle in law enforcement regarding business competition. Therefore, this research focuses on implementing indirect evidence in the construction services sector to sanction violations of business competition aspects in Indonesia. This research is descriptive and uses normative juridical research. The statutory approach (statute approach) and conceptual approach (conceptual approach) are used, supported by the secondary data divided into primary legal materials, secondary legal materials, and tertiary legal materials. The secondary data was obtained through library research collection techniques and then analysed qualitatively. The results of this study prove that indirect evidence can be used to confirm that the respondent was found guilty of tender conspiracy, indicating the practice of unfair business competition. The respondent is subject to administrative sanctions to provide a deterrent effect so as not to repeat the violation. Abstrak Pada era pemerintahan saat ini berfokus pada pembangunan infrastruktur dilakukan untuk meningkatkan daya saing di skala nasional maupun internasional. Realisasi anggaran infrastruktur tahun 2021 mencapai Rp 402,8 triliun, tumbuh 31,1% dibandingkan tahun 2020. Akan tetapi, tidak jarang penyimpangan dalam proses persiapan dan pelaksanaan pembangunan infrastruktur, salah satunya adalah terjadi persekongkolan tender di sektor jasa konstruksi. Pembuktian yang sulit menjadi hambatan dalam penegakan hukum dalam aspek persaingan usaha. Oleh karena itu, tujuan penelitian ini berfokus pada implementasi pembuktian tidak langsung (indirect evidence) di sektor jasa konstruksi, guna memberikan sanksi pada pelanggaran aspek persaingan usaha di Indonesia. Penelitian ini bersifat deskriptif dengan jenis penelitian yuridis normatif. Jenis pendekatan yang digunakan adalah pendekatan peraturan perundang-undangan (statue approach) dan pendekatan konseptual (conseptual approach). Data yang digunakan pada penelitian ini adalah data sekunder yang terbagi atas bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Data sekunder tersebut diperoleh melalui teknik pengumpulan studi kepustakaan (library research), yang kemudian data dianalisis secara kualitatif. Hasil penelitian ini membuktikan bahwa indirect evidence dapat digunakan untuk membuktikan termohon dinyatakan bersalah atas pelanggaran persekongkolangan tender, dalam praktik persaingan usaha tidak sehat. Adapun termohon dikenakan sanksi administratif untuk memberikan efek jera agar tidak melakukan pelanggaran tersebut kembali.